The pivotal role of the coronal fracture line for a new three-dimensional CT-based fracture classification of bicondylar proximal tibial fractures. Issue 10 (October 2017) - Pätzold, Robert; Friederichs, Jan; von Rüden, Christian; Panzer, Stephanie; Bühren, Volker; Augat, Peter
Abstract: Introduction: Classical fracture classifications (AO/OTA, Schatzker) are commonly used to characterize bicondylar proximal tibial fractures. However, none of these classifications allows for a treatment algorithm. The aim of our study was to use 3D appearance of these fractures in CT imaging to improve the clinical value of the classification. Materials and methods: 3D appearance of 81 CT scans of bicondylar proximal tibial fractures were systematically analyzed and were classified in 3 subtypes, based on the fracture lines orientation. The novel classification was compared for reliability and for clinical relevance with AO and Schatzker classification. Results: A total of 159 fracture lines were identified which were most frequently oriented in sagittal (89/159), and in coronal (41/159) direction. Based on the orientation of the major fracture lines three fracture types were defined. A special emphasis was drawn to the coronal fracture line of the medial plateau leading to a surgical treatment algorithm. Interobserver reliability was analyzed for all 81 patients resulting in an excellent reliability of К  = 0.936 for the 3D classification scheme compared to К  = 0.720 for the AO/OTA, К  = 0.785 for the Schatzker classification. Correlations with clinical parameters were only observed for the 3D classification. Discussion: The presented classification scheme based on the 3D geometry of bicondylar proximal tibial fractures demonstrates a good reliability of clinical relevance.